A Comparative Assessment of Basel II/III and Solvency II - Gatzert, Nadine; Wesker, Hannah (Geneva Papers on Risk and Insurance-Issues and Practice, 2012)
In the course of creating a single European market for financial services and in the wake of two financial crises, regulatory frameworks in the financial services industry in the European Union have undergone significant change. One of the major reforms has been the transition from static rules-based systems towards principles-based regulation with the intent to better capture the risk situation of an undertaking. For insurance companies, the regulatory framework Solvency II is being finalised and is scheduled for implementation after 2013. At the same time, the regulatory regime for banking, Basel II, has been revised in response to the financial crisis; the new version is Basel III. The aim of this paper is to conduct a comprehensive and structured comparative assessment of Basel II/III and Solvency II in order to detect similarities and differences as well as the benefits and drawbacks of both regimes, which might be profitably addressed. The comparison is conducted against the background of the industries characteristics and the objectives of regulation.
WiSo-Import:2015-03-26:3055
Keywords: Solvency II; Basel II/III

Managing longevity risk under adverse selection: the influence of policyholder age and contract duration - Gatzert, Nadine; Wesker, Hannah (Zeitschrift für die gesamte Versicherungswissenschaft, 2011)
In recent years, the rising life expectancy in almost all industrialized countries has led to an increasing demand by life insurers for possibilities to hedge longevity risk. Two of the most prominent alternative risk management instruments in this regard are the transfer of longevity risk to the capital market, e.g. through the purchase of mortality contingent bonds, and natural hedging, i.e. hedging longevity risk through portfolio composition. In this paper, we study the effectiveness of these risk management instruments under adverse selection, which here refers to the difference between annuitant mortality and the mortality of the population as a whole. Special emphasis is thereby placed on analyzing the impact of policyholders' age at contract inception and contract duration on the effectiveness of risk management.
WiSo-Import:2015-03-26:2684

Mortality Risk and Its Effect on Shortfall and Risk Management in Life Insurance - Gatzert, Nadine; Wesker, Hannah (Journal of Risk and Insurance, 2014)
Mortality risk is a key risk factor for life insurance companies and can have a crucial impact on its risk situation. In general, mortality risk can be divided into different subcategories, among them unsystematic risk, adverse selection, and systematic risk. In addition, basis risk may arise in case of hedging, for example, longevity risk. The aim of this article is to holistically analyze the impact of these different types of mortality risk on the risk situation and the risk management of a life insurer. Toward this end, we extend previous models of adverse selection, empirically calibrate mortality rates, and study the interaction among the mortality risk components in the case of an insurer holding a portfolio of annuities and term life insurance contracts. For risk management, we examine natural hedging and mortality contingent bonds. Our results show that particularly adverse selection and basis risk can have crucial impact not only on the effectiveness of mortality contingent bonds, but also on the insurer's risk level, especially when a portfolio consists of several types of products.
WiSo-Import:2015-03-26:3333
Keywords: Shortfall and Risk Management; mortality risk; Life insurance

The Impact of Natural Hedging on a Life Insurer's Risk Situation - Gatzert, Nadine; Wesker, Hannah (The Journal of Risk Finance, 2012)
Purpose Systematic mortality risk, i.e. the risk of unexpected changes in mortality and survival rates, can substantially impact a life insurers' risk and solvency situation. By using the “natural hedge” between life insurance and annuities, insurance companies have an effective tool for reducing their net‐exposure. The purpose of this paper is to analyze this risk management tool and to quantify its effectiveness in hedging against changes in mortality with respect to default risk measures. Design/methodology/approach To achieve this goal, the paper models the insurance company as a whole and takes into account the interaction between assets and liabilities. Systematic mortality risk is considered in two ways. First, systematic mortality risk is modeled using scenario analyses and, second, empirically observed changes in mortality rates for the last 10‐15 years are used. Findings The paper demonstrates that the consideration of both the asset and liability side is vital to obtain deeper insight into the impact of natural hedging on an insurer's risk situation and shows how to reach a desired safety level while simultaneously immunizing the portfolio against changes in mortality rates. Originality/value The paper contributes to the literature by considering the insurance company as a whole in a multi‐period setting and taking into account both, assets and liabilities, as well as their interaction. Furthermore, the paper shows how to obtain a desired safety level while simultaneously immunizing a portfolio against changes in default risk.
WiSo-Import:2015-03-26:3867
Keywords: risk management; natural hedging; mortality risk; longevity risk; life insurance